2010
DOI: 10.1099/mic.0.041715-0
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction without sex: conidiation in the filamentous fungus Trichoderma

Abstract: 2Lincoln Ventures Limited, PO Box 133, Lincoln University, Lincoln 7647, New Zealand Trichoderma spp. have served as models for asexual reproduction in filamentous fungi for over 50 years. Physical stimuli, such as light exposure and mechanical injury to the mycelium, trigger conidiation; however, conidiogenesis itself is a holistic response determined by the cell's metabolic state, as influenced by the environment and endogenous biological rhythms. Key environmental parameters are the carbon and nitrogen stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 116 publications
3
48
0
9
Order By: Relevance
“…Thus, it was proposed that photoinduction is 'remembered' while a culture is maintained in conditions that do not allow cellular growth; as soon as growth is resumed, under optimal conditions, the colony conidiates (Gressel et al, 1975;Horwitz et al, 1990). Recently, Steyaert et al (2010a) interpreted these observations as showing that oxidative processes are required for completion of the developmental programme, since there appears to be a clear differentiation between the initial photoreactions and the development of conidiation.…”
Section: Light Perception and Gene Expression At Early Stages Of The mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it was proposed that photoinduction is 'remembered' while a culture is maintained in conditions that do not allow cellular growth; as soon as growth is resumed, under optimal conditions, the colony conidiates (Gressel et al, 1975;Horwitz et al, 1990). Recently, Steyaert et al (2010a) interpreted these observations as showing that oxidative processes are required for completion of the developmental programme, since there appears to be a clear differentiation between the initial photoreactions and the development of conidiation.…”
Section: Light Perception and Gene Expression At Early Stages Of The mentioning
confidence: 99%
“…In particular, in Trichoderma, it has been shown that conidiation is regulated by light and mycelial injury (Horwitz et al, 1985;Casas-Flores et al, 2004;Steyaert et al, 2010a). Other factors that influence conidiation include C : N status, low pH, extracellular calcium, and fungal-derived volatile organic compounds (VOCs) (Nemcovic et al, 2008;Šimkovič et al, 2008;Steyaert et al, 2010a) (Fig.…”
Section: Environmental Stimuli That Induce Conidiation In Trichodermamentioning
confidence: 99%
See 1 more Smart Citation
“…The growth and conidiation of Trichoderma is influenced by some known environmental factors include the ambient pH of the medium, temperature extracellular calcium, physical injury to the mycelium and the presence of fungal-derived volatile organic compounds (Steyaert et al, 2010a). In our study, two fermentation techniques; batch and fed-batch culture, and different pH and temperature conditions affected the mycelial growth and conidiation of T. harzianum.…”
Section: Influence Of Phmentioning
confidence: 88%
“…1 mL spore suspension of T. harzianum was inoculated into Erlenmeyer flask (250 mL) containing 50 mL of liquid medium and incubated at 30 0 C for both batch and fed-batch cultures. The setup was replicated thrice after which the mycelial dry weight and spore yield was recorded after 7 days of incubation (Steyaert et al, 2010a).…”
Section: Influence Of Phmentioning
confidence: 99%